Effect of HMG-CoA Reductase Inhibition on Vascular Smooth Muscle Cells Extracellular Matrix Production: Role of RhoA - Palomino-Morales, Rogelio; Perales, Sonia; Torres, Carolina; Linares, Ana; Alejandre, Maria J. (Current Vascular Pharmacology, 2016)
Cholesterol-lowering effects apart, statins can improve the endothelial function, stabilize the atherosclerotic plaques, decrease the oxidative stress and inflammation and inhibit the thrombogenic response by means of the inhibition of isoprenoids, which serve as lipid attachments for intracellular signaling molecules. We aimed to evaluate whether the effect of statins on RhoA activity mediate extracellular matrix production, particularly affecting collagen type I, in smooth muscle cells (SMCs). Our results showed that lovastatin decreased collagen expression in primary cultured chicken SMCs as determined by incorporation of [H3]-proline, RT-PCR and immunocytochemistry. This fall was parallel to that found in Rho A activity. Similar results were found when GGTI-298, a RhoA inhibitor, was added to the culture medium. Mevalonate or geranylgeranyl pyrophosphate reverted these effects. In order to elucidate the role of Rho A in these events we transfected the cell line A10 (rat SMCs) with constitutively active (G14V) or dominant negative RhoA (T19N) constructs. The last ones showed similar results regarding collagen production that those stated above in lovastatin treated primary SMC cultures. Constitutively active RhoA transfected cells showed the opposite effects. Next we performed a promoter activity assay to exclude post-transcriptional mechanisms implicated in these studies. We found a similar pattern in col1a2 promoter activity to that found in collagen expression. Our results have demonstrated that statins regulate the activation of RhoA through its isoprenylation, which is crucial for the regulation of extracellular matrix synthesis in SMCs.
Keywords: Collagen type I